1982
DOI: 10.1159/000198760
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Histomorphometric Study of the Jejunal Mucosa in Chronic Alcoholics

Abstract: Jejunal suction biopsies of 18 chronic alcoholics (alcohol intake of more than 100 g of ethanol per day for several years) and 10 nonalcoholic control subjects were analyzed quantitatively using the microdissection technique described by Clarke. Both groups were comparable concerning age, body weight and sex. The duration of alcohol withdrawal in the alcoholics before the biopsy was taken ranged from 2 to 7 days. The mean number of villi and surface per villus was slightly lower in the jejunum of the alcoholic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…Either loss of the epithelial cells or disruption of the tight junctions will lead to an increase in intestinal permeability. Clinical studies demonstrated that acute alcohol administration can cause apparent histopathological changes in the proximal part of the small intestine, whereas chronic alcohol consumption only induces minor histopathological changes (9,12,34). Our previous study (30) also showed that intestinal histopathological alterations, such as loss of epithelial cells at the top of the intestinal villi, were associated with acute alcohol intoxication-induced intestinal barrier disruption in mice (30).…”
Section: Discussionmentioning
confidence: 87%
“…Either loss of the epithelial cells or disruption of the tight junctions will lead to an increase in intestinal permeability. Clinical studies demonstrated that acute alcohol administration can cause apparent histopathological changes in the proximal part of the small intestine, whereas chronic alcohol consumption only induces minor histopathological changes (9,12,34). Our previous study (30) also showed that intestinal histopathological alterations, such as loss of epithelial cells at the top of the intestinal villi, were associated with acute alcohol intoxication-induced intestinal barrier disruption in mice (30).…”
Section: Discussionmentioning
confidence: 87%
“…[19][20][21][22][23] In alcoholic liver disease, villous atrophy is frequently observed; reduction in villous height in relation to crypt depth and lower mucosal surface have been detected by light microscopy in alcoholics, even in the absence of cirrhosis. [24][25][26] Following the introduction of capsule endoscopy, mucosal abnormalities of the small intestine in liver cirrhosis patients with portal hypertension have been well documented and include inflammatory-like abnormalities (oedema, erythema, granularity and friability) as well as vascular lesions (cherry red spots, telangiectasias or angiodysplasia-like lesions and varices). 27 The reduced recovery of mannitol in all our study patients would be consistent with these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Morphometric studies have shown [21,23] that villus height and mucosal surface area are reduced in alcoholic as compared to nonalco holic patients. The data obtained in the present study, i.e.…”
Section: Discussionmentioning
confidence: 99%